Understanding the Drivers of Turnover Intention: A Study of Workload, Work Environment, Job Satisfaction, and Job Insecurity at PT Bank Papua - Yunike Oktovina Imbenai; Batara Maju Simatupang; R. Bambang Budhijana; Antyo Pracoyo (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2026)
The high employee turnover intention poses a serious challenge in retaining quality human resources at PT Bank Pembangunan Daerah Papua. This phenomenon is triggered by several factors, including excessive workload, unsupportive work environment, low job satisfaction, and perceptions of job insecurity among employees. This study aims to analyze the influence of workload, work environment, job satisfaction, and job insecurity on employee turnover intention. The method used in this study is quantitative with a descriptive-verificative approach. The population in this study consists of all permanent employees of PT Bank Pembangunan Daerah Papua, and the sample is determined through purposive sampling with 100 respondents. Data collection is conducted through questionnaires, and data analysis uses Partial Least Square Structural Equation Modeling (PLS SEM). The results show that workload and job insecurity have a significant positive effect on turnover intention, while work environment and job satisfaction have a significant negative effect. This means that the heavier the workload and the higher the job insecurity, the greater the employee's desire to leave. Conversely, a conducive work environment and high job satisfaction can reduce turnover intention. This research emphasizes the importance of management in fairly managing workload, enhancing job security, fostering a positive work atmosphere, and prioritizing employee welfare as part of retention strategies.